Systemic Activation of TLR3-Dependent TRIF Signaling Confers Host Defense against Gram-Negative Bacteria in the Intestine - Ruiz, Jose; Kanagavelu, Saravana; Flores, Claudia; Romero, Laura; Riveron, Reldy; Shih, David Q.; Fukata, Masayuki (Frontiers in Cellular and Infection Microbiology, 2016)
Recognition of Gram-negative bacteria by toll-like receptor (TLR)4 induces MyD88 and TRIF mediated responses. We have shown that TRIF-dependent responses play an important role in intestinal defense against Gram-negative enteropathogens. In the current study, we examined underlying mechanisms of how systemic TRIF activation enhances intestinal immune defense against Gram-negative bacteria. First we confirmed that the protective effect of poly I:C against enteric infection of mice with Yersinia enterocolitica was dependent on TLR3-mediated TRIF signaling by using TLR3-deficient mice. This protection was unique in TRIF-dependent TLR signaling because systemic stimulation of mice with agonists for TLR2 (Pam3CSK4) or TLR5 (flagellin) did not reduce mortality on Y. enterocolitica infection. Systemic administration of poly I:C mobilized CD11c+, F4/80+, and Gr-1hi cells from lamina propria and activated NK cells in the mesenteric lymph nodes (MLN) within 24 hours. This innate immune cell rearrangement was type I IFN dependent and mediated through upregulation of TLR4 followed by CCR7 expression in these innate immune cells found in the intestinal mucosa. Poly I:C induced IFN-γ expression by NK cells in the MLN, which was mediated through type I IFNs and IL-12p40 from antigen presenting cells and consequent activation of STAT1 and STAT4 in NK cells. This formation of innate immunity significantly contributed to the elimination of bacteria in the MLN. Our results demonstrated an innate immune network in the intestine that can be established by systemic stimulation of TRIF, which provides a strong host defense against Gram-negative pathogens. The mechanism underlying TRIF-mediated protective immunity may be useful to develop novel therapies for enteric bacterial infection.